ANALISA RENCANA INVESTASI ARENA WISATA PT. BINTANG ENAM DI SORONG - Paulus Perey Untajana; Anthoneta Kopong (Jurnal Pitis AKP, 2019)
This study aims to reveal the investment plan made by PT. Six Star whether it is worth doing or not. The population as well as the sample in this study were all employees, amounting to 8 people and data for 2015-2019. The tourism service procurement plan that will be built by PT. Six stars are: fishing pond, 8 units of fishing honai, 4 units of cottages, mini lake with various mini boats, mini cafe, restaurant / hall, children's playground with various games. Based on the results of research and calculations, it can be concluded that the project is feasible to run. An investment of IDR 750,000,000 at the end of the fifth year will provide a NPV of IDR 94,666,169. By calculating the payback period, it can be seen that the payback period for the investment is 3 years and 6 months from the 5 year plan. The investment age is estimated to be 20 years, so that at the end of the fifth year to the twentieth year, the company will get a minimum net profit of IDR 262,000,000 every year. In making a decision to invest in a company it is suggested that the company should immediately make a decision to undertake the project. It is recommended that even though the company is investing in the tourism arena, it still takes into account various factors such as costs, future marketing competition and economic conditions in general.